2007
DOI: 10.1161/hypertensionaha.107.090290
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control and Improved Cardiovascular Outcomes in the International Verapamil SR-Trandolapril Study

Abstract: Abstract-Uncontrolled blood pressure (BP) increases cardiovascular risk, independent of type of treatment. In this posthoc International Verapamil SR-Trandolapril Study analysis, we determined whether adverse outcomes are related to consistency of BP control, defined as the proportion of visits in which BP was in control. A total of 22 576 patients with hypertension and coronary artery disease were divided into 4 groups according to the proportion of visits in which BP was in control (Ͻ140/90 mm Hg): Ͻ25%, 25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
124
0
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(145 citation statements)
references
References 25 publications
10
124
0
11
Order By: Relevance
“…These findings are consistent with the post hoc analysis of data from the INVEST trial, which revealed that as the proportion of visits with BP control increased, there was an associated steep reduction in cardiovascular risk, independent of baseline characteristics and mean on-treatment BP. 4 Consistency of BP control offers information above and beyond mean BP. The visits in which BP is >140/90 reflect periods of absence of BP control: conceivably settings in which individuals are at higher cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the post hoc analysis of data from the INVEST trial, which revealed that as the proportion of visits with BP control increased, there was an associated steep reduction in cardiovascular risk, independent of baseline characteristics and mean on-treatment BP. 4 Consistency of BP control offers information above and beyond mean BP. The visits in which BP is >140/90 reflect periods of absence of BP control: conceivably settings in which individuals are at higher cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a post hoc analysis of individuals with hypertension and coronary artery disease enrolled in the INternational VErapamil SR-Trandolapril (INVEST) trial revealed that both proportion of visits with BP control and mean follow-up SBP were independently related to the risk of death, nonfatal MI, or nonfatal stroke. 4 Whether consistency of BP control is also important among stroke survivors remains unknown.…”
mentioning
confidence: 99%
“…4 Although each of these findings generated some interest, none could be viewed as being sufficiently newsworthy to "stop the presses." Such, however, is not the case with the study by Mancia et al 5 in this issue of Hypertension. In a posthoc analysis of the large database compiled from the INVEST Study, they have carefully evaluated a 22 576-patient cohort of patients with hypertension and coronary artery disease as to the relationship between the study's composite outcome (first occurrence of nonfatal myocardial infarction, nonfatal stroke, or death) and the proportion of study visits in which BP was controlled to a value Ͻ140/90 mm Hg.…”
mentioning
confidence: 58%
“…It is now apparent from the study of Mancia et al 5 that the functional use of office-based readings can be further fortified if BP control is viewed in a longitudinal fashion, and the better it is controlled during the period of surveillance, the more likely it is that a favorable outcome will arise. This might be best conceptualized as an area under the curve for overall BP control with the time axis being months to years rather than "day(s)," as is the case when 24-hour ambulatory BP monitoring is used.…”
mentioning
confidence: 99%
See 1 more Smart Citation